2019
DOI: 10.1097/rlu.0000000000002618
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Cancer Brain Metastasis

Abstract: Purpose: Brain metastasis (BM) in patients with differentiated thyroid cancer (DTC) are rare but associated with poor prognosis. We examined risk factors for overall survival (OS) in this population and explored the pattern of genomic alterations. Materials and Methods: Single institution, retrospective review of all patients with DTC from January 2000-November 2016, identified 79 patients for analysis. Multiple prognostic factors, including age, gender, distal metastasis (DM), diagnosis time, DM sites, BM dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
(30 reference statements)
1
2
0
1
Order By: Relevance
“…This again supports open surgery as the treatment of choice for BM, even in patients with impaired general condition [ 8 ]. While SRS could also be shown as effective in our series in line with literature reports [ 20 , 32 ], we and several authors found resection to be an independent covariate for prolonged survival [ 4 , 30 , 33 , 34 , 36 ]. In analogy to other series, our analysis does not allow for estimation of RAI therapy as a therapeutic option for BM, which has only been anecdotally reported in the literature [ 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…This again supports open surgery as the treatment of choice for BM, even in patients with impaired general condition [ 8 ]. While SRS could also be shown as effective in our series in line with literature reports [ 20 , 32 ], we and several authors found resection to be an independent covariate for prolonged survival [ 4 , 30 , 33 , 34 , 36 ]. In analogy to other series, our analysis does not allow for estimation of RAI therapy as a therapeutic option for BM, which has only been anecdotally reported in the literature [ 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…Tumor cells harboring specific genetic alterations can drive differential clinical outcomes. The TERT gene mutation was frequently observed in thyroid cancer brain metastases [ 51 ]. Additionally, BRAF mutations have been linked to the increased risk of brain metastasis at first diagnosis in such tumors [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Je nach individueller Situation können isolierte Metastasen auch durch lokale Therapien behandelt werden. Diese kann beispielsweise in Form einer Resektion [15] oder perkutanen Radiotherapie einer pulmonalen Metastase [14], einer Radiotherapie [16], Resektion [17] oder seltener einer arteriellen Embolisation [18] einer solitären Knochenmetastase, einer Radiotherapie einer Hirnmetastase [19] oder eines zervikalen regionalen Rezidivs sowie einer Radiofrequenzablation einer hepatischen Metastase [20] Wann wird die medikamentöse Tumortherapie eingesetzt?…”
Section: Radiojodrefraktäritätwie Geht Es Weiter?unclassified